Aortic valve replacement by Bjork - Shiley prosthesis.: preliminary report after one year's use in Uruguay - Nozar, José V; Abó, Juan C (Cirugía del Uruguay, 1978)
A review of results obtained in the Heart Surgery Department of our University Hospital ( Hospital de Clínicas) with aortic valve replacement by Bjork - Shiley prosthesis indicates that out of 14 patients operated in the period September 76 - October 77, ten had aortic stenosis ( acquired in 9 cases, congenital in 1), one suffered frim aortic insufficiency and three from a double Jesion. There were 2 deaths: one intraoperatory and the other in the immediate post - operatory. A third patient died suddenly 6 months after operation. Complications consisted in one hemolytic anemia and on· e_ prosthesis disfunction. Clínica! and radiologic improvement was _good in the remaining ten patients. Bjirk - Shiley's prosthesis presents advantages with respect to similar appliances.